The impact of problem-based learning on motivation and mathematics outcome for sixth-grade students - Kho, Ronaldo; Solihati, Titi; Lumbantobing, Happy (Universitas Papua, 2024)
Numerous studies have demonstrated that the implementation of problem-based learning (PBL) can enhance student motivation and learning outcomes. However, the integration of contextual media in these instructional activities remains limited. This research aims to investigate the impact of using PBL with contextual media on student outcomes, compare the differences in mathematics achievement between students taught through PBL with contextual media and those taught through conventional methods, and assess variations in student motivation between these two instructional approaches. A quasi-experimental design with a non-equivalent pretest-posttest control group was employed in this study. The participants consisted of 60 sixth-grade students, divided into an experimental group (taught using PBL with contextual media) and a control group (taught using conventional methods). Data were collected through learning motivation questionnaires and objective mathematics tests, with data analysis conducted using normalized gain scores (N-Gain) and t-tests. The results indicated significant improvements in student outcomes when taught using PBL with contextual media. Additionally, there was a marked difference in mathematics achievement between the experimental and control groups, as well as differences in student motivation between the two instructional methods. These findings suggest that implementing PBL with contextual media presents a promising strategy for enhancing both student motivation and mathematics learning outcomes.